ANALISIS TINGKAT EKSPOR KOMODITAS KOPI DI INDONESIA - Moehadi, Moehadi; Astuti, Hartiningsih; Susilo, Joko Hadi; Munawaroh, Siti Rizqiyatul; Rosida, Sahra Dwi Irma; Rizky, Vito Satria (JURNAL DIMENSI, 2025)
This study aims to analyze the influence of land area and coffee production on Indonesian coffee export volume, focusing on the five largest coffee-producing provinces: South Sumatra, Lampung, North Sumatra, Aceh, and Bengkulu. The method used was a quantitative approach with multiple linear regression analysis using EViews 10. The sample was purposively selected based on the highest coffee production in these provinces. The results show that land area negatively affects Indonesian coffee export volume, while coffee production has a positive effect. Simultaneously, these two variables contribute significantly to the variation in coffee export volume, accounting for 83.18%. This finding indicates that the increase in coffee export volume is more influenced by production effectiveness than land area alone. Therefore, the results of this study are expected to serve as a reference for the government in managing the coffee plantation sector to increase productivity and Indonesian coffee export volume.